Evaluasi Pelaksanaan Program IVA Test Di UPT Puskesmas Sei Mencirim: Tinjauan Kualitatif - H Sihotang, Oryza Sativa; Lubis, Irwansyah; Suryani, Suryani; Faiz, Muhammad Nabil; Alwini, An'nisa; Raniah, Sofia; Sumpeno, Salsabilla Julianda; Rahayu, Sri (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Early detection of cervical cancer through Visual Inspection of Acetic Acid (VIA) is an important strategy in reducing the incidence and mortality of cervical cancer in Indonesia. This study aims to describe the implementation of the VIA Test program at UPT Puskesmas Sei Mencirim and identify supporting factors and obstacles in increasing community participation through an advocacy approach. The study used a qualitative method with in-depth interviews with the Head of the VIA Test Program as a key informant. The results show that the program has been running for 12 years and is integrated in the Free Health Check (CKG) service, with IVA services every Wednesday at no cost for BPJS participants and local residents. Advocacy is conducted through collaboration with village heads and PKK mothers to increase participation, especially among women without clinical complaints. Constraints faced include social stigma and limited trained personnel. In conclusion, the implementation of the program is considered effective with the support of community-based advocacy, but needs to strengthen education and referral systems to increase screening coverage in a sustainable manner. Keywords: VIA Test, Cervical Cancer, Health Advocacy